2012
DOI: 10.1111/j.1532-7078.2012.00133.x
|View full text |Cite
|
Sign up to set email alerts
|

Relating 7‐Month‐Olds Visuo‐Spatial Working Memory to Other Basic Mental Skills Assessed With Two Different Versions of the Habituation–Dishabituation Paradigm

Abstract: This study examines the relationship between various basic mental processing abilities in infancy. Two groups of 7‐month‐olds received the same delayed‐response task to assess visuo‐spatial working memory, but two different habituation–dishabituation tasks to assess processing speed and recognition memory. The single‐stimulus group (N = 32) was familiarized with only one abstract stimulus, whereas the categorization group (N = 32) received varying exemplars of the same kind. In the categorization group, infant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…To test the role of basic perceptual information (i.e., amplitude spectrum, luminance, contrast) and configurational information (i.e., part-configuration, Gestalt information) for brain responses related to perceptual categorization in 7-month-old infants, two sets of stimuli were created: One consisting of artificial colored objects that show a clear symmetrical organization of different parts, hence revealing a specific "Gestalt" or configuration. These stimuli closely matched those designed for a behavioral study conducted earlier by Pahnke (2007; see also Ropeter & Pauen, 2013) who found that 7-month-old infants can discriminate individual exemplars, but also group them in categories. The other set consists of the very same stimuli presented in a phase-scrambled format, thus lacking any Gestalt/configurational information.…”
Section: Methodsmentioning
confidence: 57%
See 1 more Smart Citation
“…To test the role of basic perceptual information (i.e., amplitude spectrum, luminance, contrast) and configurational information (i.e., part-configuration, Gestalt information) for brain responses related to perceptual categorization in 7-month-old infants, two sets of stimuli were created: One consisting of artificial colored objects that show a clear symmetrical organization of different parts, hence revealing a specific "Gestalt" or configuration. These stimuli closely matched those designed for a behavioral study conducted earlier by Pahnke (2007; see also Ropeter & Pauen, 2013) who found that 7-month-old infants can discriminate individual exemplars, but also group them in categories. The other set consists of the very same stimuli presented in a phase-scrambled format, thus lacking any Gestalt/configurational information.…”
Section: Methodsmentioning
confidence: 57%
“…Images of 20 artificial objects (10 per category) were created that closely matched those of previous studies (Pahnke, 2007; Ropeter & Pauen, 2013) using PowerPoint © . Each configurational stimulus consisted of a central part and multiple pedal-like parts, arranged symmetrically around it.…”
Section: Methodsmentioning
confidence: 99%
“…At every fifth position, the type of stimulus changed, corresponding to 1.2 Hz (6/5 = 1.2, see Figure 2 ). Two types of stimuli were employed, red-orange/curvy shapes and blue-green/straight-edged shapes, with 10 individual exemplars of each type varying in size, color and number of pedals and parts ( Pahnke, 2007 ; Ropeter and Pauen, 2013 ). Global luminance contrast did not differ across categories ( p > 0.05).…”
Section: Analyses Of Infant Frequency Tagging Datamentioning
confidence: 99%